Distinguishing Emotions of Guilt and Shame in Psalm 51 - DiFransico, Lesley R. (Biblical theology bulletin, 2018)
Psalm 51 contains an expression of guilt and shame as the psalmist petitions God for restoration. Yet how emotions are identified or understood remains confused in recent discussion and scholarship. Drawing on modern psychological and cognitive studies of emotion, specifically the differentiation of self-conscious emotions of guilt and shame, this article will evaluate these emotions in Psalm 51 and argue that guilt is the dominant emotion conveyed while shame is less prominent. While interpreters often find self-deprecation and a sense of shame for the human condition, the psalm focuses on remorse for actions and lacks any significant negative evaluation of self. Through an analysis of the psalm, this article will discuss the function of emotion within the prayer and draw some conclusions on the significance of emotion studies for reading biblical texts.